Indigenous Constitutionalism beyond Section 35 and Section 91(24): The Significance of First Nations Constitutions in Canadian Law - Geddes, Alex (Lakehead Law Journal, 2019)
Disclaimer: This summary was generated by AI based on the content of the source document.